Effects of Chinese yam polysaccharides on the immune function and serum biochemical indexes of broilers - Deng, Jiahua; Zhang, Jinzhou; Chang, Yadi; Wang, Suli; Shi, Mingyan; Miao, Zhiguo (Frontiers in Veterinary Science, 2022)
The purpose of this experiment was to investigate the effects of Chinese yam polysaccharides (CYP) in diets on the immune function of broilers. A total of 360 (1-day-old, sex balance) healthy growing broilers with similar body weight (39.54±0.51 g) were randomly divided into control (0.00 g/kg), CYP I (0.25 g/kg), CYP II (0.50 g/kg), and CYP III (1.00 g/kg) groups. Each group contains 3 replicates with 30 broilers in each replicate, and the feeding trial lasted 48 d. The results showed that compared with the control group, the CYP II group had higher thymus index, serum IgA, complement C3, C4, IGF-I, T3, T4, INS, GH, IL-2, IL-4, IL-6, and TNF-α levels (P < 0.05) at 28, 48 d, respectively. In addition, the spleen index, serum IgM and IgG concentrations in CYP II group were higher than those in the control group at 28 d (P < 0.05). Results indicated that 0.50 g/kg CYP supplementation improved the immune function of broilers, and the CYP has a potential biological function as a green additive in broilers.